2018
DOI: 10.1371/journal.pone.0194134
|View full text |Cite
|
Sign up to set email alerts
|

Demographic transition and factors associated with remaining in place after the 2011 Fukushima nuclear disaster and related evacuation orders

Abstract: IntroductionDemographic changes as a result of evacuation in the acute phase of the 2011 Fukushima nuclear disaster are not well evaluated. We estimated post-disaster demographic transitions in Minamisoma City—located 14–38 km north of the nuclear plant—in the first month of the disaster; and identified demographic factors associated with the population remaining in the affected areas.Materials and methodsWe extracted data from the evacuation behavior survey administered to participants in the city between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…Dupont [16] suggests that two such factors would be gender and parenthood status. This corresponds to Morita et al's [8] findings regarding voluntary evacuation in Japan, which, in addition to gender and household type, found age to be a key factor. Whether the same would apply in another part of the world is not certain.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Dupont [16] suggests that two such factors would be gender and parenthood status. This corresponds to Morita et al's [8] findings regarding voluntary evacuation in Japan, which, in addition to gender and household type, found age to be a key factor. Whether the same would apply in another part of the world is not certain.…”
Section: Introductionsupporting
confidence: 89%
“…As for post-accident behavior, Zhang et al [9] found, three years after the accident, that few children and adult women returned after decontamination (e.g, 35% of children), but that elderly people returned to a high extent (86%). Moreover, those living with elderly relatives (70 years or older) were somewhat more likely (odds ratio 1.18) to remain in a pollution-affected area than those who did not [8]. Reasons stated for older people to stay are that the health risks of ionizing radiation are relatively low for them (compared to children and adolescents), that they more often than others have nostalgic feelings for their place of residence and, in tandem with gradually weakening health, and consider it economically and practically difficult to relocate and change lifestyle [9].…”
Section: Age Effectsmentioning
confidence: 99%
See 3 more Smart Citations